1987
DOI: 10.3109/00016348709020751
|View full text |Cite
|
Sign up to set email alerts
|

Small for Dates: Evaluation of Different Diagnostic Methods

Abstract: Ninety-four high-risk pregnancies were studied weekly in a prospective and longitudinal study. Uterine height, biparietal diameter (BPD), cranial perimeter (CrP) and abdominal perimeter (AbP) were measured. Amniotic fluid volume (AFV) was assessed. Of the sample selected, 58 neonates were appropriate for gestational age and 36 were small-for-date (17 symmetrical and 19 asymmetrical). The sensitivity values in diagnosis of small-for-dates were: 67% for BPD, 42% for CrP, 94% for AbP, 56% for Uterine Height and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

1988
1988
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
0
8
0
3
Order By: Relevance
“…19 · 25 Our results particularly contrasted with those of Brown I!J and Fescina 20 who described AC sensitivity values of 90(/l, 'to 100(/l with little difference between symmetrical and asymmetrical growth retardation. 20 However, comparisons between studies are difficult since there are so many differences in ultrasound technique, interval between scan and birth, growth curve standards, percentile reference values, definition of growth retardation, and patient sample. Indeed, out data has shown that the performance of AC and EFW in identifying fetal growth retardation is influenced by the intrinsic characteristics of the patient sample.…”
Section: Discussionmentioning
confidence: 99%
“…19 · 25 Our results particularly contrasted with those of Brown I!J and Fescina 20 who described AC sensitivity values of 90(/l, 'to 100(/l with little difference between symmetrical and asymmetrical growth retardation. 20 However, comparisons between studies are difficult since there are so many differences in ultrasound technique, interval between scan and birth, growth curve standards, percentile reference values, definition of growth retardation, and patient sample. Indeed, out data has shown that the performance of AC and EFW in identifying fetal growth retardation is influenced by the intrinsic characteristics of the patient sample.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of head and abdominal circumferences over diameters are stated by various authors [1,2,5,8,10,11]. PAPIERNIK has demonstrated the importance of abdominal parameters over head parameters [19].…”
Section: Discussionmentioning
confidence: 99%
“…Certains demandent plusieurs mesures successives [13,20,35], ou étudient la dynamique de la courbe ; beaucoup d'équipes disposent d'une courbe de HU dans leur dossier [13,42].…”
Section: Valeurs Et Courbes De Référenceunclassified